Pemanfaatan Kain Blacu Sebagai Dummy Sebagai Material Produk Tas Wanita Dengan Penerapan Teknik Makrame - Eirene, Charisma; Endah Santoso, Ratna (Pusat Penerbitan LPPM ISI Bali, 2024)
A dummy is an item that resembles the original in shape, appearance, and type, or it can be said that a dummy is a replica made from calico fabric. Dummy fabric is fabric that has been shaped into clothing with dimensions that match the design and is usually collected and stored as a reference or sample. The making of this work was done by maximizing the potential of calico fabric as a reused dummy. Dummy is reprocessed into a rope that will be used to make a complementary fashion product in the form of a women's bag (handbag) by applying the macrame knotting technique. Handbags are an option in women's daily lives as a fashion complement because of their varied shapes as well as functions that are easily mixed and matched in various situations. The application of the macrame technique to the handbag also provides its own uniqueness and aesthetic value, so that the shape and appearance of the bag is more attractive and different from existing bags. The application of the method used is the creation of S.P Gustami which in the process of making through three stages including exploration, design and realization. The realization of the work is in the form of three designs of women's bags by utilizing calico cloth as a dummy with the application of macramé technique.